Cutaneous manifestations of COVID-19: experience from a tertiary care center for COVID-19 management in South India - Mariyath, Olasseri K. R.; Sukumarakurup, Sreekanth; Samad, Koyakutty A.; Devi, Keerankulangara; Nikhil, George; Minu, Ulpurath; Mekha, Premachandran; Shaan, Mohamed (International Journal of Research in Dermatology, 2020)
Cutaneous manifestations observed in COVID-19 include maculopapular rash, urticaria, pseudo chilblain, vesicles, livedo reticularis, petechiae, erythema multiforme-like, symmetric drug related intertriginous and flexural exanthem (SDRIFE)-like and pityriasis rosea-like lesions. Maculopapular rash involving the trunk and sparing palms and soles is the most common cutaneous manifestation reported in COVID-19 patients. We report cutaneous manifestations in six COVID-19 patients from the corona isolation ward and intensive care unit of a tertiary care center for COVID-19 management in Kerala, South India. The skin lesions observed were urticaria (two patients), atypical maculopapular rash with urticarial and erythema multiforme-like lesions, eruptive pseudoangiomatosis, exaggerated insect bite reaction and acute localized exanthematous pustulosis (ALEP)-like lesions. To the best of our knowledge atypical maculopapular rash with urticarial and erythema multiforme-like lesions, eruptive pseudoangiomatosis and acute localized exanthematous pustulosis-like lesions are not reported in COVID-19.